Teaching judo efficiently : applied nonlinear pedagogy - Särkilahti, Lauri (2020)
Research in motor learning has advanced immensely over the last two decades, but there is relatively little transfer to pedagogy (Chow 2010). Nonlinear models of learning have been proposed to be more effective than traditional linear models of learning (Lee et al. 2014; Gray 2018; Nathan, Salimin & Shahril 2017). However, combat sports and self-defense are still often taught according to a traditional model by having students emulate a movement pattern demonstrated by an expert (Körner & Staller 2017). This study aims to bridge that gap for judo by answering two fundamental questions: How can judo be taught using nonlinear pedagogy and what kind of principles practitioners can use to help them apply nonlinear pedagogy in teaching judo. To answer the questions, a training program consisting of twenty 60-minute training sessions was created to teach various aspects (e.g. techniques and tactics) of judo according to nonlinear pedagogy. An intervention was then conducted where an advanced group of fifteen judokas was taught according to that program. The group consisted of 13 men and two women and on average the participants had practiced judo for 14 years before the intervention. The training sessions were coached and observed by the author of the study. The observation was conducted using participant observation (Tuomi & Sarajärvi 2018, 70; Vilkka 2018). As the result of the study, the observations were synthesized with theoretical knowledge to create six principles to help practitioners utilize nonlinear pedagogy in their coaching. The principles were: 1. Teach how a technique works – not how it’s done, 2. Train like you fight, 3. Simplification – controlling the tactical complexity of judo, 4. Individualization: same technique – various difficulties, 5. Teach gripping as a system and 6. Encourage problem solving by asking questions. In this study nonlinear pedagogy was found to be a suitable method for teaching judo and its key principles were adapted to a judo-specific form to act as a practical tool for coaches and teachers. This study provides insight into how judo could be taught using nonlinear pedagogy, but further research is needed to study its effects and compare it to a more traditional approach to provide justification for a shift in teaching paradigm.